Legal Regulation Of Agricultural Land Reclamation In The Land Code Of The Republic Of Uzbekistan - Eldor Rashidovich Kurbonov (International Scientific and Current Research Conferences, 2020)
This article deals with the legal regulation of land reclamation in agriculture, its necessity, the role of the Land Code of the Republic of Uzbekistan in the legal regulation of land reclamation,and also this article deals with issues such as the state of legal regulation of land reclamation in the Land Code, improving the legal regulation of land reclamation in agriculture.